Quantitative dual-energy CT as a nondestructive tool to identify indicators for fossilized bone in vertebrate paleontology - Hamm, Charlie A.; Hampe, Oliver; Mews, Jürgen; Günter, Christina; Milke, Ralf; Witzmann, Florian; Savic, Lynn J.; Hecht, Lutz; Meister, Sabine; Hamm, Bernd; Asbach, Patrick; Diekhoff, Torsten (Scientific reports, 2022)
Dual-energy computed tomography (DECT) is an imaging technique that combines nondestructive morphological cross-sectional imaging of objects and the quantification of their chemical composition. However, its potential to assist investigations in paleontology has not yet been explored. This study investigates quantitative DECT for the nondestructive density- and element-based material decomposition of fossilized bones. Specifically, DECT was developed and validated for imaging-based calcium and fluorine quantification in bones of five fossil vertebrates from different geological time periods and of one extant vertebrate. The analysis shows that DECT material maps can differentiate bone from surrounding sediment and reveals fluorine as an imaging marker for fossilized bone and a reliable indicator of the age of terrestrial fossils. Moreover, the jaw bone mass of Tyrannosaurus rex showed areas of particularly high fluorine concentrations on DECT, while conventional CT imaging features supported the diagnosis of chronic osteomyelitis. These findings highlight the relevance of radiological imaging techniques in the natural sciences by introducing quantitative DECT imaging as a nondestructive approach for material decomposition in fossilized objects, thereby potentially adding to the toolbox of paleontological studies.